Giving Everyone a Fish: COVID-19 and the New Politics of Distribution - Webb, Christopher (Anthropologica)

(untitled) (University of Victoria, 2021)
In response to widescale job losses produced by the COVID‑19 pandemic, states have drastically expanded social protections, primarily through cash transfer programs. Drawing from James Ferguson’s notion of distributional politics, this reflection analyzes the meaning of this rapid global expansion of the welfare state and the political opportunities it provides. Based on two seemingly disparate cases, South Africa and Canada, I suggest that these expansions provide valuable opportunities for rethinking existing approaches to livelihoods, labour and social protection. These interventions also provide political possibilities through which a more radically redistributive politics can be articulated. In both contexts, state responses have provoked new challenges, dialogues, and experiments in distribution at multiple scales, from the neighbourhood to the nation state. This reflection calls for deeper inquiry into the multiple meanings of cash transfers and the political openings they provide. Finally, it provides guiding questions for future anthropological inquiry into livelihoods and social protection.